Working Paper 2: Multistakeholder initiatives to combat money laundering and bribery (Basel Institute on Governance Working Papers, 2006)
Intensified economic globalisation has had positive and negative effects. It has left nation states struggling to deal with the negative fall-out. National regulation against abuses has, however, proven increasingly ineffective, especially since companies have the freedom to move their hazardous activities to under-regulated areas.States have stepped up cooperation and coordination on a bilateral as well as a multilateral basis: international organisations and treaties become more and more relevant to the regulation of international trade relations. However, the traditional instruments of international law are frequently considered too cumbersome and slow.Increasingly international law is created by unconventional means: ‘task forces’ prove to be far more expedient, since they prefer ‘soft law’ to treaty law. Political enforcement by peer-pressure becomes more relevant than by juridical instruments (e.g. courts and tribunals). Furthermore, regulation goes well beyond law-making by legislators and government bodies; non-state actors contribute extensively, especially in the area of regulating international trade relations.
Keywords: Collective Action; multi-stakeholder partnerships; anti-corruption initiatives; anti-corruption compliance